Teaching practices and student achievement : report of first-year findings from the "Mosaic" study of systemic initiatives in mathematics and science - Klein, Stephen P., 1938- (RAND, 2000)
In our increasingly technological society, improving students' performance in mathematics and science has become a critical challenge. During the 1990s, the National Science Foundation funded a series of Systemic Initiatives designed to change the way these subjects are being taught in schools throughout the country. These initiatives sought to align all aspects of the educational system in support of ambitious curriculum and performance standards, with particular emphasis on teacher training and professional development to promote effective changes in instructional practice. States, urban school districts, and consortia designed programs to implement reforms that were consistent with NSF's goals, and in 1996, RAND undertook a study to investigate the relationships between student achievement in mathematics and science and the use of these new instructional practices. The authors examined six sites that were implementing systemic reforms during the 1996-97 school year, and a similar set of sites during the 1997-98 school year. This report presents the results of theiranalysis of data from the first year of the study. The findings provide some (albeit weak) support for the hypothesis that the reform instructional practices are associated with improved student achievement in both mathematics and science. However, as with most large-scale field studies, there are many factors that may have artificially increased or decreased the observed effect sizes. Nevertheless, the consistency of the results across sites is encouraging. Data from the second year of the study will provide additional evidence to aid in the interpretation of these findings.